Livestock Business Development Strategy Beef Cattle In Indonesia - Ni Made Ayu Gemuh Rasa Astiti (Eduvest - Journal of Universal Studies, 2022)
Indonesia is a potential country for the development of a cattle breeding business because it is supported by the availability of land resources that are used as feed sources. The success of developing a cattle breeding business is highly dependent on the selection and application of a strategy that is appropriate to the characteristics of the region. The purpose of this study was to determine the development strategy for beef cattle farming in Indonesia. The research approach used is qualitative with data analysis using the Miles and Huberman interactive analysis model. Miles and Huberman's interactive analysis model includes 3 main things, namely data reduction, data presentation, and drawing conclusions. The results of the study with SWOT analysis show that Strength-Opportunities (SO) are more recommended as a beef cattle farming business development strategy in Indonesia